Extension program on the control of bovine fasciolosis in West Java, Indonesia - Eny Martindah; A Kusumaningsih; S Widjajanti; S Partoutomo; B Frank; Suhardono . (Indonesian Center for Animal Research and Development (ICARD), 1998)
An extension program to control fasciolosis in cattle and buffalo was undertaken in collaboration with officers of the District of Livestock Services (DLS) and farmer organizations in the Surade district of West Java. Control strategies were based on results of extensive epidemiological studies on fasciolosis in this area over the past 4 years. Recommendations included: (1) preventing animals grazing harvested rice fields adjacent to a village or cattle pen; (2) feeding stock only the top two-thirds of freshly cut rice stalks; (3) mixing cattle or buffalo faeces with manure of ducks or chicken naturally infected with Echinostoma revolutum, before using them as fertilizer in rice fields; and (4) a single treatment with triclabendazole in July, about 6 weeks after harvest of the last seasonal rice crop. Farmers were surveyed in January 1996 to determine their level of knowledge about fasciolosis. The extension program commenced in February, soon after planting the second seasonal rice crop in four villages. At first, leaflets were distributed to farmers, and posters were displayed in each village to provide basic information. Following discussions with village leaders, groups of farmers met in each village to discuss the advantages they saw in each strategy, ways they could implement them, and to identify socio-economic constraints that needed to be overcome. Taped interviews were prepared for a local radio station and the farmer groups. In August, final survey was conducted to determine the change in knowledge and attitudes that had occurred as a result of the extension program. Bennett’s hierarchy was used at each stage to evaluate the effects of inputs and activities. Farmers adopted the techniques of cutting and feeding rice-stems 2/3 above water-level, and isolating cattle from rice-fields during harvest time, as these appeared to be beneficial in social and economic terms; but they rejected the two other practices where they perceived that socio-economic costs exceededbenefits. Key words : Fasciolosis control, extension program, cattle, buffalo